(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
الملخص: يعتبر التحكم في مهارات ا البحث المعلوماتية، مقياس ضروري للحاضر والمستقبل لكل متعلم، لاستخدام تكنولوجيا الألفية الثالثة وهو بمثابة حجر الزاوية لتكوين أفراد واعون معلوماتيا، يعرفون كيف يحصلون على المعلومة التي يحتاجونها و يعرفون كيف يتواصلون ويسترجعون المعلومات من مصادرها بالمكتبات ومن مواقع الشبكة العالمية للمعلومات ويقيمون معلومات المسترجعة قبل توظيفها واستثمارها بفعالية. تهدف هذه الدراسة إلى تسليط الضوء على أهمية اكتساب المهارات البحث المعلوماتية بالنسبة للطلبة وتحديدا درجة تحكم طلبة الدراسات العليا في العلوم الإنسانية والاجتماعية ببعض جامعات الغرب الجزائري في هذه المهارات. الكلمات المفتاحية :المهارات البحث المعلوماتية ،مصادر المعلومات ،دراسات العليا،البحث الوثائقي الرقمي، المهارات المعلوماتية. Abstract: The control of informational research skills is considered a necessary measure for the present and the future for every learner to use the technology of the third millennium, and it is the cornerstone for the formation of information-aware individuals, who know how to obtain the information they need and know how to communicate and retrieve information from sources in libraries and from the World Wide Web, and they master the evaluation of information technology. And criticism of information before using it and investing it effectively. This study aims to shed light on the importance of acquiring informational research skills for students, specifically the degree to which graduate students in humanities and social sciences control these skills in some universities in western Algeria. Keywords: Information research skills, information sources, postgraduate studies, digital documentary research, information skills